Pengembangan Kelompok Wanita Tani (KWT) Melati Mini menjadi Kelompok Tani yang Mandiri dan Berkembang - Mirnawati Mirnawati; Yurniwati Yurniwati; Zuhri Syam; Arief Arief (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
This community service activity aims to increase the knowledge about the formulation of low-priced quail rations and the economic aspects of the business, i.e. entrepreneurship, marketing and business development. The quail farmers incorporated in Women Farmer Group named KWT Melati Mini Koto Lua located in Pauh District, Padang City. They were also given knowledge and training on maggot farming of Black Soldier Fly larvae as a protein source for fish meal replacement for quail's ration. This activity impacts the development of community quail farming which is a manifestation of Andalas University's concern as a higher education institution for the community around campus and improves the performance of community service and the application of innovation by Andalas University. The stages of implementing the activities were counselling on quail maintenance management, developing unconventional rations, applying ration formulation technology and low-priced rations. The activity was followed by providing Hammer Mill machines for ration processing by farmers. The activity has impacted farmers' knowledge about feed ingredients and low-priced ration formulations for quail, the use of unconventional feed ingredients as quail feed ingredients, maggot farming as a protein source feed ingredient for poultry and quail rearing management. Counselling in entrepreneurship has provided farmers knowledge about various things related to business managing that are useful for developing quail farming businesses. Implementing rations by processing their low-cost rations for quail breeders showed that the rations provided were of good enough quality. The ration application in quail farming did not affect the production of quail eggs, reducing the cost of rations, which can ultimately increase farmers' income.